The Role of Islamic Religion Education in the Transformation of the Madrasah Tsanawiyah in Ponorogo Towards a Child-Friendly Schoolroom: Case Study Implementation of a Child Friendly School Program - Ratna Utami Nur Ajizah; Irfan Jauhari (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This study examines the role of Islamic Religious Education in the transformation of Madrasah Tsanawiyah in Ponorogo towards child-friendly learning environments, focusing on the implementation of the Child-Friendly School Program. This program is designed to create a safe, comfortable, and supportive learning environment that fosters the holistic development of students. The research focuses on how Islamic Religious Education contributes to the development of students' moral and spiritual values and how this approach is applied in daily school practices. The research methodology includes observations, in-depth interviews with teachers and students, and analysis of related documents. The results show that integrating Islamic Religious Education into the curriculum and school activities positively impacts the formation of students' character and behavior. Additionally, the program successfully increases students' active participation in the learning process and creates an inclusive and responsive school climate that meets children's needs. In conclusion, Islamic Religious Education plays a crucial role in supporting the transformation of Madrasah Tsanawiyah into child-friendly learning environments, in line with holistic and inclusive educational goals.